Digital and media literacy : connecting culture and classroom - Hobbs, Renee (Thousand Oaks, Calif. : Corwin Press, 2011)
'Renee Hobbs, one of the nation's leading authorities on media literacy education and an active presenter, offers real-life examples of teachers who incorporate media literacy education into 7-12 curriculum through creative uses of mass media, popular culture, and online social media. Media Literacy Education will give educators the tools to help secondary students develop the competencies associated with media literacy: the ability to access, analyze, evaluate and communicate messages in a wide variety of forms. Hobbs provides examples and vignettes in the area of English language arts, literature, social studies, health education, and the fine and performing arts. Teachers will learn how to select meaningful media'texts' for use in the classroom and how to recognize the'teachable moment' in dialogue and discussion about mass media and popular culture'-- Provided by publisher.
Machine generated contents note: PrefacePublisher's AcknowledgmentsAbpit the AuthorAccess1. Why media Literacy2. Research as Authentic InquiryAnalyze3. Critical Questions, Close Reading4. The Power of RepresentationCreate5. Composing with Media Across the CurriculumReflect6. Protection and Empowerment7. Life OnlineTake Action8. What in the World: Teaching with Current Events9. Infusing Media Literacy Across the CurriculumEndnotes and BibliographyIndex.
Includes bibliographical references and index.
Keywords: Mass media in education -- United States; Media literacy -- Study and teaching (Secondary) -- United States; Popular culture -- Study and teaching (Secondary) -- United States